Analyzing additional wind effects to better optimize high-rise structural design - VanNierop, Benjamin L. (My University, 2026)
The current ASCE 7-22 provides a comprehensive framework for determining the baseline wind forces on high-rise structures for static pressures. However, it overlooks dynamic wind effects such as vortex shedding and dynamic amplification. This report aims to address the additional wind effects not specified in ASCE 7-22. Through calculations for both static and dynamic winds, a comparison was made showing that the addition of dynamic wind loads not considered in ASCE 7-22 altered the overall wind load and modified the base shear and sidewall force from static pressures. Due to this, suggested design considerations for high-rise buildings were developed to better match the new base shear and adjusted sidewall forces with all wind effects in consideration. To show how these new design considerations can be applied, a steel-framed structure located in Miami, Florida, will be analyzed. The structure will have a 120 ft x 120 ft footprint with a height of 480 ft. This case study will be used to determine the wind forces along the structure as defined in ASCE 7-22, as well as to determine any changes in base shear and sidewall forces additional wind effects applies to the structure.
Keywords: Dynamic amplification; Vortex shedding; High-rise structure case study